Saatleri Ayarlama Enstitüsü'nde Toplumsal - Kurumsal Eleştiri ve İroni - Günday, Rıfat (Gökkubbe, 2007)
Tanpınar, Türk kültürü ve yaşamını dikkatle gözlemleyen bir yazardır. Saatleri Ayarlama Enstitüsü adlı romanında, tarihsel dönemler ve değişim süreci çerçevesinde toplumsal gerçekleri, bireylerin yaşadığı değerler karmaşası ve kimlik bunalımını, kurumların işleyiş mantığını çarpıcı boyutlarıyla yansıtmaktadır. Ustaca kurgulanmış bir öyküdeki olayların anlatımında eleştirinin yanında ince bir ironiye sıkça başvurmaktadır yazar. Tanpınar is an autor who observes Turkish culture and Turkish life style very carefully. In his novel called The Time Regulation Institute, in a frame of historical periods and changing process he reflects social realities, value confusion and identity erisis experienced by individuals, and the way how the institutions work in their striking dimensions. The author frequently applies to irony in addition to criticism white teliing the events of story fictionaliced.
Social- Institutional Criticisme and Irony in The Time Regulation Institute
Keywords: Türk Kültürü; Değişim; Kimlik Bunalımı; Eleştiri; İroni; Turkish Culture; Change; Identity Crisis; Criticism; Irony